PENGARUH VARIABILITAS TOPOGRAFI DAN SIFAT FISIK TANAH TERHADAP PRODUKSI KENTANG DI KECAMATAN BUMIAJI, KOTA BATU - Andhika, Yosi; Sudarto, Sudarto; Widianto, Widianto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Soil erosion causes a loss of nutrients in the soil and is evident in the agricultural areas of Batu City, primarily due to the steep or very steep topography. So it will affect the level of production. Determination of the effectiveness of observation was based on four classes of slope: 0-8%, 8-15%, 15-30%, and >30% at various altitudes: <1,100 m, 1,100-1,300 m, 1,300-1,500 m, 1,500-1,700 m, and >1,700 m above sea level 40 observation points. Geostatistical analysis with ArcMap software was conducted to determine the pattern of semivariograms. The results of this study indicated that the slope, altitude, and organic matter affect the yield of potatoes. The resulting formula is y = 11.845 - 0.258x1 + 0.007x2 + 2.454x3, where y is the potato productivity, x1 is slope, x2 is altitude, and x3 is the organic C, with r value is 0.87 and R2 value = 0.74. The highest potential production of potatoes in Bumiaji reached 33.06 t ha-1, and the lowest was only 7.12 t ha-1. Available land planted with potatoes can produce 35,891 t of potato, with average productivity reaching 24.6 t ha-1.